Pollution Resulting From Waste Accumulation at the Binjai City Landfill and Management Efforts - Nazla Ghassani Irtifa (Universitas PGRI Madiun, 2026)
The problem of waste accumulation at the Binjai City Landfill has become an environmental issue that requires serious attention due to the increase in waste generation in line with population growth, urban development, and increased community economic activity. The landfill, located in Mencirim Village, still uses an open disposal system, which is unable to control the daily volume of waste and causes soil, water, and air pollution. This study aims to explain the factors causing waste accumulation, the forms of pollution that arise, and their impact on the community around the landfill, as well as to identify sustainable waste management strategies. The research method used is descriptive qualitative through literature studies, regulatory reviews, local government reports, scientific articles, and field observations that produce a comprehensive picture of the condition of the landfill. The results show that the accumulation occurs due to the volume of waste exceeding the storage capacity, the absence of waste sorting at the source, the high dependence of the community on plastic, and the weak implementation of waste reduction policies. This accumulation produces leachate that contaminates groundwater and surface water, hazardous gases that cause pungent odors, and an increase in the population of disease vectors such as flies and rats. The impacts include respiratory disorders, skin diseases, a decline in land economic value, increased health costs, and a decline in the quality of life of the community. Based on these findings, this study recommends waste sorting at the household level, the development of recycling-based waste treatment facilities, community empowerment, the transformation of landfills into sanitary landfills, and the strengthening of law enforcement. The results of this study are expected to form the basis for the formulation of more effective and environmentally friendly waste management policies for the Binjai City Government.